(untitled) (Iranian Journal of Kidney Diseases, 2013)
Hemolytic-uremic syndrome (HUS) is a rare life-threatening disorder characterized by microangiopathic hemolytic anemia, thrombocytopenia, and impaired renal function. A thrombotic microangiopathy underlies the clinical features of HUS. In the majority of cases, HUS follows an infection with toxin-producing bacteria such as verotoxin-producing Escherichia coli. In some cases, HUS is not preceded by a clinically apparent infection, and therefore, is named atypical HUS. The prognosis of atypical HUS is poor. While mortality approaches 25% during the acute phase, end-stage renal disease develops in nearly half of patients within a year. Evidence is accumulating that complement activation through the alternative pathway is at the heart of the pathophysiology leading to atypical HUS. Genetic abnormalities involving complement regulatory proteins and complement components form the molecular basis for complement activation. Since microvascular thrombosis is a quintessential feature of atypical HUS, complements and the coagulation system must work in tandem to give rise to the pathologic alterations observed in this condition. Here, a brief discussion of clinical and morphologic features of atypical HUS is followed by a concise presentation of the complement and coagulation systems. The interplay between complements and the coagulation system is graphically highlighted. Last but not least, conventional and emerging therapies for atypical HUS are outlined.